Access, use and attitudes regarding information and communication technologies among older adults during the COVID-19 pandemic - Cerda Díez, Maria Fernanda; Ureta, María del Pilar; Pavez, Isabel; Benavides, Cristóbal; Inostroza-Quezada, Ignacio; Epstein, Leonardo D. (Revista Española de Comunicación en Salud, 2023)
Introduction: The COVID-19 pandemic highlighted the digital divide among older adults. Their everyday needs and mobility constraints forced them to go online, challenging older adults with limited access to Information and Communication Technologies (ICTs) and scarce digital abilities. Objective: This study explores factors influencing older adults' use and perception of ICTs during the pandemic. Methodology: We conducted a survey of vulnerable elderly individuals in Santiago, Chile (N=251) and followed up with face-to-face interviews with 20 participants. Results: The findings indicate that frequent smartphone use among older adults is positively correlated with their perception of comfort, usefulness, control over the device, and willingness to use it. Active users exhibit higher confidence levels and engage in a broader range of online activities, while moderate users feel less inclined to bridge the digital gap, experiencing a sense of exclusion. Conclusion: The study highlights the importance of perceived control in shaping smartphone usage among older adults and underscores the interplay between attitudes and technology adoption. Despite some limitations, this research offers valuable insights into the perspectives of non-users and proxy users, as well as the barriers to internet access during a crisis.
Keywords: Internet use and perception; smartphone; older adults; vulnerability; mixed methods